Geodetic Flare Triangulation - , Fr. National Geographical Institute (The International Hydrographic Review, 2015)
The principle governing the geodetic method of simultaneous observations of parachute flares is not new. Frequently referred to in English as "Flare triangulation", this method had previously been used in certain long distance geodetic connexions, but the accuracy of the results was comparatively poor owing to difficulties of synchronized observations. The studies and experiments conducted at the Institut Géographique National in the last two years have resulted in the development of a simple operation procedure as well as a simple equipment which gave very accurate results which compare favourably with other methods that are more expensive and more complicated.